Precision, Privacy, Protection: The New Triad of Healthcare Data Integrity - Onwuegbuchulam, Chukwudi; Chibu-Obinna, Onyinye Ugochi; Ezebunanwa, A. C. (European Journal of Applied Sciences, 2025)
Digital transformation in the healthcare domain has significantly shed light on the question of data integrity and the critical role that the triad of precision, privacy, and protection plays in ensuring data integrity. The paper addresses complex issues, including the need to maintain a structural balance that provides the honest, effective, and ethically justifiable handling of health data. The accuracy of information and its application in clinical practice and research, patient privacy, legal protection of patients, and safeguards against increasing cyber threats. Even with these two foundations of continuously growing data integrity and security, trade-offs between data utility, accessibility, and other aspects remain possible. New and emerging technologies, such as blockchain and privacy-preserving technologies (PPTs), include homomorphic encryption and Federated learning. Data, in turn, is facilitated by such technologies, which enhance the protective layers of privacy and data integrity, but also introduce challenges of scale, interoperability, and an expensive nature, as well as ethical concerns, including algorithmic bias. This paper aims to establish interdisciplinary, open, and data-driven patient processes, including dynamic consent, to foster social trust and social justice, thereby addressing the gaps in scalability, interoperability, and equitable access to digital health technologies. The necessity of creative, data-driven, collaborative, and patient-centered interdisciplinary innovations requires vigilance to maintain the protective integrity of Cardinal Health data.